Developing a Unified Model for Indicators for the Financial Analysis of Public Sector Entities - Kamarauskienė, Irma (Buhalterinės apskaitos teorija ir praktika, 2021)
Financial analysis is an analysis of an entity’s financial performance and position to assess its achievements and prospects, as well as, to provide the financial managers with quality up-to-date information that will help them make the right decisions in the future. The financial analysis concerns the forecasting, accounting, planning and control of certain economic activities. However, financial analysis is mainly linked to private sector entities. The issues of financial analysis of public sector entities in scientific work are addressed in a fragmented way. There is still a lack of not only scientific but also practical work to analyse the issues of financial analysis in the public sector.The article presents a modified model for the financial analysis system, the analysis indicators to be applied and their combinations. In addition to traditional indicators, the presented system includes indicators of public interest and development. The system may be used for analysing the state of public sector entities. Its results may be useful for different users of information in making appropriate decisions.Research object: the financial analysis of public sector entities. The purpose of the research is to establish a unified and modified model of the system for conducting the financial analysis of the public sector entities. Tasks: to describe the logical sequence of financial analysis after analysing and summarising the theoretical and practical aspects of the analysis of the financial position of public sector entities; to identify and group indicators for analysing the financial position of the public sector. Research methods: analysis of scientific works, methods of information grouping, comparing, detailing, generalizing.
Keywords: public sector entity; public sector; financial analysis; financial analysis indicators